Pelatihan Membuat Soal Matematika Secara Daring Menggunakan Aplikasi Kahoot - Aima, Zulfitri; Yunita, Alfi; Febriana, Rina (LPPM Universitas Bumigora, 2023)
In the world of education, it is currently commonly known as learning media that can be used as teaching aids for teachers to make it easier for students to understand the material being taught. Learning media can clarify the presentation of messages and information from teachers to students so that they can facilitate and improve learning processes and outcomes. Learning media can also overcome the limitations of the senses, space and time. One form of media is Kahoot. Kahoot is a game-based learning platform that uses educational technology in schools and other educational institutions. Kahoot is in the form of a multiple choice quiz game application or a survey of opinions and opinions of students or members of public institutions conducted online via a browser. learning through Kahoot is very easy to implement. Kahoot can be played through different browsers to browsers installed on student gadgets. The Kahoot application is very interesting, because the teacher can create quizzes by inserting pictures or videos in the problem so that it can attract students' attention. Kahoot is because the question is equipped with an image or video. Even using short expressions, accompanied by music that is appropriate for their age. Not only that, kahoot can be a form of online interactive media.